MEMPELAJARI PENGGUNAAN TUNGKU LIMBAH KAYU SENGON (Parasaerianthes falcataria) UNTUK PENGERINGAN PAPANNYA - Tjutju Nurhayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The sengon wood waste fired stove was installed, to supily energy into certain length of circulating duct of the dryirlg chamber. The utilization of wet slabs (moisture content 163.3 percent) in a wood stove produced drying air tempe- rature in the chamber at 30ᵒC. When jointing board waste (moisture content 12.16 percent) was used to fire the stoue the drying temperature of 70°.C was achiued.The efficiency of the wood waste fired stoue was 39.46 percent, calculated on the basis of the energy produced by sengon wood waste burned, and the energy consumed by the drying wood i.e 3.641 and 1.397 GJ.